ANALISIS PENCEMARAN LOGAM BERAT TIMBAL DI BADAN SUNGAI BABON KECAMATAN GENUK SEMARANG - Putri Budiastuti; Mursid Rahadjo; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Babon River is a river that flows in the Genuk industries region and has decreased water quality due to contaminated residential waste and industrial waste. The industry includes coal heap, garment industry, leather tanning industry, light brick industry, plastic industry, and industrial ice cubes. This research aims to determine the lead content in the sediments and biota Sulcospira testudinaria along the Babon river from the mouth to the dam of Pucang Gading. This research was a descriptive observational research with quantitative approach. The results of supporting variable are water temperature 260C-280C, water pH 6, dissolved oxygen 2,2 mg/l – 3,6 mg/l, the salinity of fresh water from 0,20/00 – 0,60/00, Salinity brackish water 300/00 reseacrh sites. Analysis of water quality data is using Pollution Index. The result of using AAS is obtained levels of lead sediments in Babon river is the highest for 7,256 mg/kg and the lowest is 4,170 mg/kg. Levels of lead heavy metals Sulcospira testudinaria biota is the highest 2,403 mg/kg and the lowest is 1,8 mg/kg. The pollution index was lightly polluted with the amount of 1,96 which was the highest in Penggaron Kidul and the lowest is 1,13 in border between Banjardowo and Trimulyo. It can be concluded lead in sediments does not exceed the quality standards Sediment Quality Guideline 2003, while levels of lead heavy metals Sulcospira testudinaria biota has exceeded food quality standard SNI 7387:2009.